Evaluasi dan Perancangan Sistem Informasi Pemeliharaan Sarana Prasarana di Fakultas Ilmu Komputer Universitas Brawijaya - Widianto, Akbar (Jurnal Ilmiah Administrasi Publik, 2016)
In the maintenance activities that reliably many factors affecting among others the procurement, use and maintenance of the facility, which is supported by the mechanism of maintenance work. One of the problems that occur in the maintenance of office equipment is sometimes if the goods are in a separate location, so that the monitoring process becomes difficult. Similarly, in the Faculty of Computer Science Brawijaya University, data collection is still done manually. The results of this research that there are several factors at issue in the handling of the speed of improvement of infrastructure in Filkom is a Maintenance Process Goods and Infrastructure, Systems and Technology At present, the computer is not there DBMS technology. System Design maintenance information infrastructures are built according to user needs defined.